Mediating Effects of Perceived Service Quality in Relationship between Perceived Management Information System and competitive advantage in telecommunication sector, South Darfur state- Sudan - Ahmed, Alamin Mohammed Adam; Abdallah, Magbola AbdAljabar Hissin; Essa, Murtda Yagoup Abdalla; Mohamed, Musa Salih Omer (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at identify the impact of Perceived Service Quality in relationship between Perceived Management Information System and competitive advantage in the telecommunication sector in Sudan, South Darfur state. , the model of the study was built on the assumptions based on literature based on previous studies, the study used Non-probability sample , questionnaire to collect data were distributed to a number of 160 questionnaires valid for analysis at a rate of 78%, Used (AMOS) program, Cronbach's Alpha to test reliability and used path analysis to test the hypotheses of the study. The results of the study showed that there is a positive relationship between Perceived Management Information System and competitive advantage, there is a positive effect Perceived Management Information System on Perceived Service Quality. And the Perceived Service Quality is mediate the relationship between Perceived Management Information System and competitive advantage, also have a theoretical and practical implications and having recommendations and suggestions for future researches.
Keywords: Perceived Service Quality; Perceived Management Information System; comparative advantage